LUNG CANCER CLASSIFICATION USING KNN CLASSIFIER - Vishnu Vardhan Reddy, Bana; R. , Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
Lung cancer is cancer of the lungs that starts. Two spongy organs in your chest are your lungs, which you ingest inhaling oxygen and releasing carbon dioxide as you exhaust. In the early stages of lung cancer, it does not usually cause signs or symptoms. Lung cancer symptoms and signs typically arise as the disease progresses. The early diagnosis is required for lung cancer classification. In this study, the automatic classification of lung cancer is discussed. Initially, the input images are given to the energy feature for feature extraction, and the K-Nearest Neighbor (KNN) classifier is used for classification. The performance of the proposed system produces a classification accuracy of 91% using a KNN classifier.